Notch receptor expression in Trypanosoma cruzi‐infected human umbilical vein endothelial cells treated with benznidazole or simvastatin revealed by microarray analysis. (22nd January 2020) - Campos‐Estrada, Carolina; González‐Herrera, Fabiola; Greif, Gonzalo; Carillo, Ileana; Guzmán‐Rivera, Daniela; Liempi, Ana; Robello, Carlos; Kemmerling, Ulrike; Castillo, Christian; Maya, Juan Diego
Abstract: Chagas disease is a vector‐borne disease caused by the protozoan parasite Trypanosoma cruzi . Current therapy involves benznidazole. Benznidazole and other drugs can modify gene expression patterns, improving the response to the inflammatory influx induced by T. cruzi and decreasing the endothelial activation or immune cell recruitment, among other effects. Here, we performed a microarray analysis of human umbilical vein endothelial cells (HUVECs) treated with benznidazole and the anti‐inflammatory drugs acetylsalicylic acid or simvastatin and infected with T. cruzi . Parasitic infection produces differential expression of a set of genes in HUVECs treated with benznidazole alone or a combination with simvastatin or acetylsalicylic acid. The differentially expressed genes were involved in inflammation, adhesion, cardiac function, and remodeling. Notch1 and high mobility group B1 were genes of interest in this analysis due to their importance in placental development, cardiac development, and inflammation. Quantitative polymerase chain reaction confirmation of these two genes indicated that both are upregulated in the presence of benznidazole.